2007
DOI: 10.1902/jop.2007.060247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Full‐Mouth Scaling and Root Planing in Conjunction With Systemically Administered Azithromycin

Abstract: It was shown that full-mouth SRP using systemically administered azithromycin was a clinically and bacteriologically useful basic periodontal treatment for severe chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
143
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(150 citation statements)
references
References 32 publications
(75 reference statements)
5
143
0
2
Order By: Relevance
“…Most researchers have focused on the use of AZM in the treatment of chronic periodontitis (Gomi et al, 2007;Haffajee et al, 2007Haffajee et al, , 2008Mascarenhas et al, 2005;Morozumi et al, 2010;Oteo et al, 2010;Plaza et al, 2003;Pradeep et al, 2008;Sampaio et al, 2011;Smith et al, 2002;Yashima et al, 2009). To the best of our knowledge, only one clinical trial has used AZM in the treatment of aggressive periodontitis (Haas et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Most researchers have focused on the use of AZM in the treatment of chronic periodontitis (Gomi et al, 2007;Haffajee et al, 2007Haffajee et al, , 2008Mascarenhas et al, 2005;Morozumi et al, 2010;Oteo et al, 2010;Plaza et al, 2003;Pradeep et al, 2008;Sampaio et al, 2011;Smith et al, 2002;Yashima et al, 2009). To the best of our knowledge, only one clinical trial has used AZM in the treatment of aggressive periodontitis (Haas et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The study investigators reported on 6 major groups of antimicrobials: amoxicillin and metronidazole combination therapy, 18,44,45,47,50,55,60 metronidazole, 39,52,61 erythromycin analogues (azithromycin 39,46,49,51,[56][57][58][59] and clarithromycin 53 ), moxifloxacin 48 (a fourth-generation fluoroquinolone antibacterial agent), and others (for example, tetracycline 20,43,54 and doxycycline 22,48,62 as the antimicrobial dose of doxycycline, not to be confused with SDD, which is covered in a separate section). The variety of dosing regimens used for each systemic antimicrobial drug is described elsewhere.…”
Section: Moderatementioning
confidence: 99%
“…Compared with SRP alone, SRP plus systemic antimicrobials resulted in a 0.35-mm mean gain in CAL (95% CI, 0.20-0.51) ( Figure 5). 18,20,22,39,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] We judged the overall level of certainty in the evidence to be moderate on the basis of the evidence profile in Table 3.…”
Section: Moderatementioning
confidence: 99%
“…Several systemic antibiotics or antibiotic combinations have been used as an adjunct therapy in the treatment of chronic periodontitis, such as the use of AMX, MTZ, DOX, and AZM. 35,26,37,55 For non-smokers, several studies have shown clinical benefits, such as a reduction of PD and a CAL gain, to using systemic antibiotic therapy associated with non-surgical therapy. 56,57,58 However, the variability of dosing, frequency, time of use, and choice of antibiotics led to a consideration of the need to establish protocols for an effective therapy.…”
mentioning
confidence: 99%